Simulation study of 4-bit and 8-bit Kogge Stone parallel prefix adder circuit characteristics using SILVACO: article - Ya' Acob@ Selamat, Siti Rohaya; Al-Junid, Syed Abdul Mutalib (2011)
This paper describes the design of Radix-2, Radix-3 and Radix-4 of 4-bit and 8-bit Kogge Stone Parallel Prefix Adder (KSPPA) architecture. The objective is to study and investigate the effects of these different radix to the various characteristics of KSPPA in tem1s of logical depth, number of transistors used, propagation delay, and average power consumption. The simulation study is carried out by Gateway SILVACO EDA Tools software and the design is mapped for a O. l 8µm CMOS technology with 1.8V of supply voltage. The result shows that for 4-bit KSPP A, the Radix-4 is the best design while Radix-2 is the worst design, as Radix-4 reduced logical depth by 50%, reduced transistors used as much as 23%, 3% faster, and lower average power consumption by I .2%. Then for 8-bit KSPPA, Radix-3 is the best design while Radix-2 still the worst design, as Radix-3 reduced logical depth by 50%, reduced transistor used as much as 18%, 9% faster, and lower average power consumption by 6.6%.